Community Perception on Waste Management (Case Study: Bumi Maluku Lestari Waste Bank, Ambon City) - Ivakdalam, Lydia Maria; Far Far, Risyarth A. (Agrikan: Jurnal Agribisnis Perikanan, 2021)
Waste bank is one alternative that can be done in overcoming the problem of waste management. The Bumi Lestari Maluku Waste Bank was established in order to develop social awareness for the environment, especially in waste management and reforestation. The purpose of the study was to describe the management pattern of the Bumi Lestari Maluku waste bank in Ambon City and to find out public perceptions on economic, social, and environmental aspects related to waste management. The research was conducted in Laha Village, Teluk Ambon District, Ambon City. Data were collected by means of a census of 30 customers of the Bumi Lestari Maluku waste bank who were used as research respondents. The types of data used are primary data and secondary data. Primary data was obtained through interviews with respondents using a questionnaire and secondary data was obtained from a relevant source from the Department of the Environment, the National Statistics Agency. The method used is descriptive quantitative analysis using a Likert scale. Research shows that the Bumi Lestari Maluku Waste Bank has a system and working method starting from sorting organic and inorganic waste in the household, depositing waste to a waste bank, weighing waste, recording the amount of waste savings to the results into rupiah value and waste by collectors. Community perception of Bumi Lestari Maluku waste management economically with additional income, socially increasing social interaction, and creating a clean and healthy environment.